Dental status between assisted reproductive technology and natural conceived children: a comparative pilot study - Mohd Kenali, Norzaiti; Sukmasari, Susi; Mohd, Farah Natashah; Mohamad Basir, Mohd Syazwan Aidid; Lokhman, Mohd Firdaus (SciDoc Publishers, 2021)
Objectives: ART children were proven to have low birth weight and some birth defects. However, limited number of studies found concerning dental status of ART children. This research aimed to determine oral health practice and dental status between Assisted-Reproductive (ART) and Natural Conceived (NC) children. Materials And Method: This cross-sectional study consisted of 34 subjects, 17 were ART children and 17 NC children as control. Intraoral examination was conducted and orthopantomogram (OPG) radiograph were obtained from the subjects. Any abnormalities of tooth development such as number and tooth colour were recorded. Oral hygiene practice such as tooth brushing frequency and supervision from the parents during tooth brushing were identified. Caries experience of both groups were recorded using dmft for deciduous teeth and DMFT for permanent teeth. Descriptive analysis, Bivariate analysis were done using Mann-Whitney’s test and Spearman rho test. Results: Most of the participants were girls (58.8%) and majority were aged of 7 – 8 years old (47.1%). 70.6% of ART group used intra-uterine insemination (IUI) technique while 29.4% used in-vitro fertilization (IVF). There was one hypodontia case found in each group. Caries experience in primary teeth showed significantly lower in the ART group with p < 0.05. Conclusions: There was a comparable case of hypodontia in ART and NC group. However, caries experience (dmft) of children in ART group was found significantly lower than NC group.